Islamic psychospiritual theory according to the perspective of Maqasid al-Sharia - Muhammad Afiq Abd Razak,; Mohd Syukri Zainal Abidin,; Muhammad Safwan Harun, (Penerbit Universiti Kebangsaan Malaysia, 2023)
Islamic psychospirituality is a discipline that combines psychological and spiritual elements based on Islamic principles. The Islamic psychospiritual approach that emphasises on the purificaiton process of the soul (tazkiyyah alnafs) becomes a necessity for man in order to ensure the well-being of his life and achieve happiness in this world and the Hereafter. This need is linked rather closely to the objective of legislating sharia law or the more popularly used term maqasid al-sharia in order to accomplish the good for all human beings. However, there are still gaps in the literature that discusses thoroughly the relationship between Islamic psychospirituality and maqasid al-sharia. Therefore, this article was conducted to discuss Islamic psychospirituality according to maqasid al-sharia. This study was conducted using full library research method for data collection and qualitative approach for data analysis. Based on the anylisis it was found that the relationship between Islamic psychospirituality and maqasid al-sharia can be seen from two views namely from the debates of al-kulliyat al-khams and al-wasilah wa al-ghayat towards the achievement of al-sa’adah (happiness) which is maqasid al -sharia al-’ammah (general maqasid sharia). Ultimately, Islamic psychospirituality plays a very important role in the development of insaniah which eventually leads to the guaranteed preservation of alkulliyat al-khams which is the main core of maqasid al-sharia.